New Data Analysis of the Stroop Matching Task Calls for a Reevaluation of Theory - Goldfarb, Liat; Henik, Avishai (Psychological Science, 2006)
In Stroop matching tasks, participants indicate whether the color of an object matches the meaning of a color word printed in color. Previously in this journal, Luo (1999) concluded that interference between two incongruent representations of the same attribute (ink color) occurs prior to the response stage. However, this conclusion was based on questionable data analysis. We suggest analyzing the data by separating "same" and "different" responses and then analyzing three congruency conditions within the "different" responses: (a) congruence between word color and word meaning, (b) congruence between word color and object color, and (c) incongruence between word color, word meaning, and object color. In an experiment similar to Luo's, such an analysis revealed that responding was slowest in the first condition. This pattern of results does not fit with previous conclusions regarding this task, but rather indicates that task conflict and response competition contribute to interference. This analysis has implications for matching tasks other than the Stroop matching task.